Tecnologias móveis em saúde na gestação : análise da qualidade de aplicativos para smartphones - Faria, Taímy Castrillon da Costa (2021)
ABSTRACT: Background: Mobile health apps targeting antenatal care have become part of the pregnancy experience. These technologies are use as an important strategy in health, however, the data on the information provided by pregnancy apps is still very limited, mainly referring to quality and especially these means, since their quality is determined by questions of software and not according to the content served. Objective: This study aimed to evaluate the quality of the content of mobile applications for pregnancy care in a form and language available in Portuguese in the main online stores, following as a reference to World Health Organization content for prenatal care, as well as, evidence on the subject. Method: The study was characterized as research with a quantitative, transversal-descriptive approach. A search was carried out in the virtual stores of the Android (Play Store) and iOS (App Store) operating system, using the keywords “prenatal” and “pregnancy”. Results: 18 applications were included in the study and the findings were presented in the form of two manuscripts. The first aimed to describe the applications available to the lay public, for care related to the gestational period and found that the applications for pregnancy care, for the most part, were developed in other countries (66.67%) and made available in the Portuguese version in Brazil with comprehensive content on prenatal care, few were developed by professionals in the area (83.33%) and most did not provide the source of the content (55.58%). The second manuscript analyzed the quality of content delivered by pregnancy care apps, rated as excellent in terms of usability testing, based on the WHO guidelines for antenatal care and current references. The results showed that the applications adhered to the content present in the WHO recommendations, but not all of them were by what was proposed by the guidelines and other reliable references. Many applications provide incorrect and/or conflicting information and recommendations, mainly because they are developed in other countries and are made available to other locations, with different realities. Conclusion: It is concluded that although there is an excellent number of applications aimed at pregnancy care, few are of quality and fit the reality of the Brazilian population. More studies are needed to assess the quality of the content available in these apps, as many are not developed based on scientific references and there is currently not enough evidence and regulation to support the safety and effectiveness of these apps. It is necessary to monitor and create applications by health professionals, based on evidence, mainly according to the context of the country in which the application will be made available.